The PA Protein Directly Contributes to the Virulence of H5N1 Avian Influenza Viruses in Domestic Ducks - Song, Jiasheng (American Society for Microbiology (ASM), 2011)
During their circulation in nature, H5N1 avian influenza viruses (AIVs) have acquired the ability to kill their natural hosts, wild birds and ducks. The genetic determinants for this increased virulence are largely unknown. In this study, we compared two genetically similar H5N1 AIVs, A/duck/Hubei/49/05 (DK/49) and A/goose/Hubei/65/05 (GS/65), that are lethal for chickens but differ in their virulence levels in ducks. To explore the genetic basis for this difference in virulence, we generated a series of reassortants and mutants of these two viruses. The virulence of the reassortant bearing the PA gene from DK/49 in the GS/65 background increased 10(5)-fold relative to that of the GS/65 virus. Substitution of two amino acids, S224P and N383D, in PA contributed to the highly virulent phenotype. The amino acid 224P in PA increased the replication of the virus in duck embryo fibroblasts, and the amino acid 383D in PA increased the polymerase activity in duck embryo fibroblasts and delayed the accumulation of the PA and PB1 polymerase subunits in the nucleus of virus-infected cells. Our results provide strong evidence that the polymerase PA subunit is a virulence factor for H5N1 AIVs in ducks.